Деякі проблеми розробки люмінесцентного трансформатора для кремнієвих сонячних елементів - Azovskyi, V. A.; Yashchuk, V. M.; Bulavko, G. V.; Ishchenko, A. A. (Publishing house "Academperiodika", 2020)
Aromatic polymer composites are characterized by the high absorption and luminescence excitation in the short-wave interval of the solar radiation spectrum from about 200 nm. Therefore, they can be used to enhance the spectral sensitivity of semiconductor solar cells, including silicon-based ones, at short waves. When such a composite absorbs light, there arise Frenkel excitons in it, which are responsible for the transfer of the excitation energy to molecular traps. The latter emit light in the spectral region of maximum solar cell sensitivity. The results obtained demonstrate a possibility to develop a luminescence converter on the basis of a polymeric composite, thus increasing the photocurrent generated by Si-based solar cells.